A new platform for post-marketing surveillance and real-world evidence data collection for substance-based medical devices - Cioeta, Roberto; Cossu, Andrea; Giovagnoni, Emiliano; Rigoni, Marta; Muti, Paola (Frontiers in Drug Safety and Regulation, 2022)
The recent European Union (EU) Regulation 2017/745 on medical devices (MDs) has improved the classification of MD, revised their approval process and post-marketing evaluation of safety and effectiveness, promoting transparency and post-marketing oversight in Europe. Thus, the new regulation can better ensure patient’s safety and can provide new opportunities for therapeutic innovation. In addition, the new regulation has directly included and defined MD made of substances or of combinations of substances (SBMDs). The impressive growth of MD, including SBMDs, marketed over the recent years has likely been a relevant factor fueling this change. The MD regulation is requiring a major effort from both industry and notified bodies to comply with its provisions. Manufacturers should produce sufficient clinical evidence that a MD, under normal conditions of use, provides adequate performance, and that the foreseeable risks and frequency of adverse events (AEs) have an acceptable minimum rate, taking into account the benefits provided . We describe how we implemented the Post-Marketing Surveillance (PMS) system of SBMDs to properly dealing with post-market monitoring and confirmation of their safety and performance, including AEs and the benefit-risk evaluation, as required by the 2017/745 Regulation. The two pillars of this novel system are: 1- passive vigilance, i.e. spontaneous reporting, and 2- active Post-Marketing Clinical Follow-up (PMCF) activities, that systematically gather, record, and analyze Real World Data (RWD) on performance, quality, function, use, tolerability and safety of a MD , collected through a dedicated, structured web platform. The active PMCF is achieved through a process of generation, validation and administration of digital questionnaires to all stakeholders, i.e. patients, physicians, both general practitioners and specialists, and pharmacists. The technology, potential use, advantages and limitations of this large source of RWD is also discussed.